الأدب القصصي الملايوي: ترجمة ودراسة وصفية نقدية من خلال مجلة ديوان سسترا 1990 – 1992م - Khalid bin Ludin (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This study examines Malaysian language short stories in translation through a critical and analytical review of three texts. It considers the significance of Dewan Bahasa dan Pustaka as the incubator of Malay language and literature. It plays a vital role in elevating the status of Malay culture, especially the art of storytelling. Dewan Sastera, a magazine published by Dewan Bahasa dan Pustaka, has been publishing short stories and everything related to Malay literature since the start of the magazine. The texts selected are Islam-oriented stories that were published in this magazine between 1990 and 1992. These stories are as categorized heroic political, religious, or social. The three selected stories are more Islam-oriented as compared with other stories identified for this research and they fall under at least one of these categories. These stories are also analytically and critically reviewed for their aesthetic value. The objectives behind the writing of Malay short stories are examined in terms of content and Islamic viewpoint. This thesis is also a commentary on the history and development of Malay short stories, as well as the Malay short story in contemporary Malaysia.